Urea enhances the yield and quality of bio-oil produced from corncob through pyrolysis - Sakina Ibrahim Bello; Taofik Olatunde Uthman; Serdar Surgun; Abdullahi Muhammad Sokoto (Scientific Reports)
Abstract As global demand for fossil fuels rises amidst depleting reserves and environmental concerns, exploring sustainable and renewable energy sources has become imperative. This study investigated the pyrolysis of corncob, a widely available agricultural waste, using urea as a catalyst to enhance bio-oil production. The aim was to determine the optimum urea concentration and pyrolysis temperature for bio-oil yield from corncob. A series of experiments were conducted at varying temperatures (350 °C, 400 °C, and 450 °C) and urea concentrations (0%, 5%, 10%, 15%, and 20%) to assess their impact on bio-oil yield, chemical composition, and energy content. Fourier Transform-Infrared Spectroscopy, Gas Chromatography-Mass Spectrometry (GC–MS), Ultimate Analysis, and High Heating Value (HHV) analyses were employed to evaluate the quality of bio-oil produced. Results indicate that a 10% urea concentration at 400 °C improves bio-oil yield from 49.33 to 54.66%. FT-IR analysis revealed enhanced absorption in key functional group regions, including O–H, N–H, C–H, C=O, and C–O, for bio-oil treated with 10% urea compared to untreated bio-oil. Ultimate analysis indicates that urea treatment improved bio-oil quality by increasing carbon (84.80–86.40%), nitrogen (2.29–2.68%), and oxygen (7.22–8.31%) contents while reducing hydrogen (5.09–2.38%) and sulfur (0.62–0.20%) contents, with improvement in the HHV from 36.12 to 37.12 MJ/kg. GC–MS analysis further revealed the presence of nitrogenous compounds, notably siloxanes in the bio-oil produced with urea infusion. This research highlights the potential of urea-catalyzed pyrolysis as a viable method for converting corncob into high-energy bio-oil, offering a promising alternative to traditional fossil fuels while addressing sustainability and environmental impact challenges.